K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

11 tháng 12 2019

\(A=\sqrt{x^2-2x+1}+\sqrt{x^2+4x+4}\)

\(=\sqrt{\left(x-1\right)^2}+\sqrt{\left(x+2\right)^2}\)

\(=|1-x|+|x+2|\ge|1-x+x+2|=3\)

11 tháng 12 2019

\(x\sqrt{x+\frac{1}{2}+\sqrt{x+\frac{1}{4}}}=2\)

\(\Leftrightarrow x\sqrt{\left(\sqrt{x+\frac{1}{4}}+\frac{1}{2}\right)^2}=2\)

\(\Leftrightarrow x\sqrt{x+\frac{1}{4}}+\frac{1}{2}=2\)

\(\Leftrightarrow x\sqrt{x+\frac{1}{4}}=\frac{3}{2}\)

Làm nốt

10 tháng 12 2019

Ta có: \(A=\left|x\right|.\sqrt{1-x^2}\le\frac{\left(\left|x\right|\right)^2+1-x^2}{2}=\frac{1}{2}\)

Đẳng thức xảy ra khi \(\left|x\right|=\sqrt{1-x^2}\Leftrightarrow x^2=\frac{1}{2}\Leftrightarrow x=\frac{1}{\sqrt{2}}\text{ hoặc }x=-\frac{1}{\sqrt{2}}\)

P/s: Em ko chắc.

15 tháng 5 2024

\(\dfrac{ }{ }\)\(\dfrac{ }{ }\)

10 tháng 12 2019

\(4x^4-4x^3+4=4y^2\)

Ta có:

\(\left(2x^2-x-1\right)^2< 4x^4-4x^3+4=4y^2< \left(2x^4-x+3\right)^2\)

\(\Leftrightarrow\left(4x^4-4x^3+4\right)=\left(\left(2x^2-x\right)^2;\left(2x^2-x+1\right)^2;\left(2x^2-x+2\right)^2\right)\)

Làm nốt